1995
DOI: 10.1038/bjc.1995.398
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine gene transfection into tumour cells reduced tumorigenicity in nude mice in association with neutrophilic infiltration

Abstract: :awa LUniveritY. 13-1, Takara-machi, Kana:awa 920. Japan.Summarv To studv the effect of localised secretion of chemokines on tumour growth. the genes for human (hu interleukin 8 (IL-8). hu-MCP-1 (NICAF). hu-MIP-12 (LD78). murine (mu)-MCP-1 (JE). mu-MIP-lx or mu-MIP-2 A-ere introduced. v-ia mammalian expression vectors. into Chinese hamster ovarv (CHO) cells. and the abilitv of transfected cells to form tumours in vivo uas evaluated. The production of hu-IL-8. hu-MIP-lx or mu-MIP-lx bv transfected clones did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 34 publications
4
69
0
Order By: Relevance
“…42 IL-6 is frequently produced in glioblastoma cells, 43 whereas IL-8 is a chemokine, which promotes the directional migration of neutrophils, basophils and T-lymphocytes into the tumor growth area. 44,45 We speculate that upregulation of these immune response genes may enhance the general immunity of the treated mice to tumor cells by increasing the release of cytokines and infiltration of immune effector cells into the tumor growth areas. It is worth noting that the PMN infiltrates may account for the tumoricidal effects induced by rAAV-hTERTC27 treatment.…”
Section: Raav-htertc27 Treatment Induces Differential Expression Of Gmentioning
confidence: 98%
“…42 IL-6 is frequently produced in glioblastoma cells, 43 whereas IL-8 is a chemokine, which promotes the directional migration of neutrophils, basophils and T-lymphocytes into the tumor growth area. 44,45 We speculate that upregulation of these immune response genes may enhance the general immunity of the treated mice to tumor cells by increasing the release of cytokines and infiltration of immune effector cells into the tumor growth areas. It is worth noting that the PMN infiltrates may account for the tumoricidal effects induced by rAAV-hTERTC27 treatment.…”
Section: Raav-htertc27 Treatment Induces Differential Expression Of Gmentioning
confidence: 98%
“…16,[18][19][20] Since IL-8 is a critical regulator of neutrophil activation and migration, 21 we postulate that the biological effects of IL-8 in vivo may be associated with its ability to regulate neutrophil infiltration. To test this hypothesis, we used immunocytochemistry to detect neutrophil on frozen tumor tissues.…”
Section: Il-8 Suppression Reduces Neutrophil Infiltration Into Tumorsmentioning
confidence: 99%
“…Tumor volume (mm 3 ) was calculated using the formula: tumor size 5 ab 2 /2, where 'aÕ is the larger and 'bÕ is the smaller of the 2 dimensions. 16 To determine the stability of the IL-8 interference in vivo, blood was collected from the tails of nude mice bearing tumors at 2, 4 and 6 weeks after injection. The blood was centrifuged at 2,000 rpm for 10 min, and serum was collected and stored at 280°C until further testing by ELISA assay as described earlier.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Some workers have reported the effect of transduction of the MCP-1 gene into fibroblasts and cancer cells (Rollins and Sunday, 1991;Bottazzi et al, 1992;Hirose et al, 1995). Rollins and Sunday (1991) showed a suppressive effect of JE gene-transfection on the tumorigenicity of CHO cells, but Bottazzi et al (1992) found that melanoma cells producing MCP-1 were more tumorigenic than control cells.…”
Section: Discussionmentioning
confidence: 99%